Quality of life in painful temporomandibular disorders onset: a systematic review of outcome measure clinimetrics and predictive properties. (22nd July 2021) - Shaffer, Stephen M.; Emerson, Alicia J.; Burr, Meghan; Einhorn, Leah; Naze, Garrett S.
Abstract: Background: Many self-report outcome measures (SROMs) exist for measuring Quality of Life (QoL) in patients with painful temporomandibular disorders (TMD). However, it is uncertain which SROM(s) is/are best suited for research and clinical practice. Objectives: The aims were to (1) identify clinimetrically sound SROMs for QoL in patients with painful TMD and (2) determine if impaired QoL has diagnostic or prognostic value for this population. Methods: PRISMA guidelines were utilized during a systematic search of: CINAHL, Dentistry & Oral Science Source, PsychALL, PubMed, Scopus, and Web of Science. Studies involving adult populations with painful TMD who were assessed for QoL were included. Risks of biases were examined. Results: 23 studies were included; 8 clinimetric studies primarily validated language translation whereas other studies were diagnostic ( n  = 14) or prognostic ( n  = 1). Of the eight identified SROMs assessed, only the Oral Health Impact Profile (OHIP)-49, OHIP-TMD (OHIP-22), OHIP-14, and the SF-36 are valid and reliable in painful TMD. In regards to the diagnostic studies, both region- and non-region-specific QoL SROMs associated presence of TMD with poor QoL. Study heterogeneity prohibited meta-analysis. The SF-12 demonstrated prognostic capabilities. Conclusion: For region-specific SROMs, the OHIP-49, -TMD/-22, and −14 are available to clinicians in multiple languages to capture QoL in patients with painful TMD. For clinicians interested in overall QoL, the SF-36 was found to be valid in this population. Emerging evidence has shown that baseline QoL can predict future outcomes.